Determination of tocopherol and carotenoid contents in ST muscle of suckling lambs using fresh or lyophilised muscle - Blanco M.; Molino F.; García-Durillo M.; Ripoll G.; Lobón S.; Sanz A.; Joy M. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The aim of the study was to compare tocopherol and carotenoids contents in lyophilised and fresh meat to reduce the time and chemical reactives used in the analytical procedure. Twenty ewe-lamb pairs grazed on pastures (723, 570, 147 and 6.6 μg/g DM of β-carotene, lutein, α- and γ-tocopherol contents respectively; Grazing) and 19 pairs were raised indoorswith ewes receiving pasture hay (24, 100, 11 and 1.1 μg/g DM of β-carotene, lutein, α-, and γ-tocopherol contents respectively; Hay). After slaughter (live-weight: 11 ± 0.8 kg), both Semitendinosus muscles were excised to determine carotenoids and tocopherol contents in lyophilised or fresh meat. The contents of α-tocopherol and lutein determined using lyophilised meat were 2.8-fold and 21.3-fold greater than using fresh meat (P<0.001). The content of β-carotene was undetectable whereas γ-tocopherol content was not detected in lyophilised meat and near 0 in fresh meat. Regarding the effect of the ewe’s diet, α-tocopherol content was greater in grazing than in hay treatment, regardless of the method of extraction (1.35 vs. 0.83 μg/g FM in lyophilised and 0.56 vs. 0.21 μg/g FM in fresh meat). Lutein content was greater in grazing than in hay treatment lambs in lyophilised meat (0.28 vs. 0.08 μg/g FM) but did not differ in fresh meat. The content of γ-tocopherol content was greater in grazing than in hay treatment lambs in fresh meat (0.003 and 0.001 μg/g FM, respectively, P<0.05). Consequently, it would be more appropriate to determine α-tocopherol and lutein contents in lyophilised meat, although γ-tocopherol content was not detectable.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)